Stability and Bioaccessibility of β-Arbutin in Simulated Digestion Conditions - Łukasz Sęczyk; Danuta Sugier; Piotr Sugier (Applied Sciences)
In this study, the effects of physicochemical and biochemical digestion conditions on β-arbutin stability and bioaccessibility were investigated. β-Arbutin, at doses that correspond to its natural occurrence in plant materials (i.e., 1–100 mg), was subjected to gastric and intestinal electrolyte treatments (application of physicochemical factors) or the whole digestion process (application of physicochemical and biochemical factors). Its content in in vitro bioaccessible fractions was determined using high-performance liquid chromatography (HPLC), and percentage bioaccessibility was calculated. The study shows very high stability and bioaccessibility of β-arbutin in a wide range of applied concentrations. Especially at doses ≥7.5 mg, bioaccessibility was close to 100% regardless of the stage of digestion and the type of treatment (electrolyte treatment or the whole digestion process). The assessment of phytochemicals in terms of their stability and interactions with the digestion environment can help in the future evaluation of their applicability for therapeutic purposes. The high bioaccessibility of β-arbutin within its multifunctional biological activity makes it a promising substance for phytomedicinal applications.